Identification and functional analysis of glyoxal oxidase gene from rubber tree anthracnose - Xuemei Xian; Kunmeng Li; Hui Liu; Zhenhui Wang; Kun Yuan; Yiyu Hu; Chengtian Feng; Meng Wang; Chunhua Lin; Qiguang He; Yu Zhang (Plant Protection Science, 2023)
Glyoxal oxidase (GLOX, EC 1.2.3.15) is a class of hydrogen peroxide synthases involved in lignin degradation. Several GLOX genes of biotrophic and necrotrophic phytopathogenic fungi have been confirmed to contribute to fungal growth, development, and pathogenicity. However, the composition, sequence characteristics and functions of genes in the GLOX family of hemi-biotrophic phytopathogenic fungi remain poorly understood. This study identified a GLOX-encoding gene CsGLOX in the hemi-biotrophic phytopathogenic fungus Colletotrichum siamense by bioinformatics analysis and PCR cloning. The encoded protein contains a signal peptide and five cell wall stress-responsive component (WSC) domains at the N terminus, followed by a catalytic structural domain (AA5_1). CsGLOX-deficient mutants were constructed by homologous replacement, which significantly increased the formation of conidia and reduced the pathogenicity and the high-osmotic stress tolerance of the fungus. However, the deletions did not influence fungal filamentous growth. This study proposes that the CsGLOX gene is involved in pathogen conidial formation, pathogenicity, and osmotic stress response, which deepens our understanding of the pathogenic mechanism of hemi-biotrophic phytopathogenic fungus C. siamense.